Quality Assurance, Open and Distance Learning, and Australian Universities - Reid, Ian C. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
Open and distance education has integrated quality assurance processes since its inception. Recently, the increased use of distance teaching systems, technologies, and pedagogies by universities without a distance education heritage has enabled them to provide flexible learning opportunities. They have done this in addition to, or instead of, face-to-face instruction, yet the practice of quality assurance processes as a fundamental component of distance education provision has not necessarily followed these changes. This paper considers the relationship between notions of quality assurance and open and distance education, between quality assurance and higher education more broadly, and between quality assurance and the implementation of recent quality audits in Australian universities. The paper compares quality portfolios submitted to the Australian Universities Quality Agency by two universities, one involved in distance education, the other not involved. This comparison demonstrates that the relationship is variable, and suggests that reasons for this have more to do with business drivers than with educational rationales.